Electrical safety a guide to the causes and prevention of electrical hazards - Adams, J. Maxwell (London, United Kingdom Institution of Engineering and Technology, 1994)
This book explains the hazards associated with electricity in its many forms, including electromagnetic radiation. It describes methods of reducing risks to health and to the environment, giving rules and codes of practice to be followed. Guidelines are also given for the use of electrical equipment in specialised environments (such as locations subject to explosive gases and flammable dusts), the guarding of machine tools and the control of earth currents. Human safety and care for the environment are of increasing concern and the broad scope of the book makes it essential reading for those involved in engineering and technology at all levels - no specialised knowledge of electro-technology is presumed. It is a reference book for personnel responsible for their company's safety policy and for municipal authorities (particularly in commonwealth countries) and other bodies concerned with technical training, industrial development and planning.
Also available in print version.
Electronic reproduction.
Keywords: Electrical engineering -- Safety measures; Electronic books